2018
DOI: 10.1371/journal.pgen.1007172
|View full text |Cite
|
Sign up to set email alerts
|

Novel genetic polymorphisms associated with severe malaria and under selective pressure in North-eastern Tanzania

Abstract: Significant selection pressure has been exerted on the genomes of human populations exposed to Plasmodium falciparum infection, resulting in the acquisition of mechanisms of resistance against severe malarial disease. Many host genetic factors, including sickle cell trait, have been associated with reduced risk of developing severe malaria, but do not account for all of the observed phenotypic variation. Identification of novel inherited risk factors relies upon high-resolution genome-wide association studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 35 publications
2
68
0
2
Order By: Relevance
“…These enable detection of single nucleotide polymorphisms (SNPs) throughout the genome that show statistical associations with pathogen infection. In addition to identifying associations at known immune loci (Fellay et al, 2007;He et al, 2015;Wong et al, 2010), GWAS approaches may reveal novel candidate genes (Fu et al, 2012;Ravenhall et al, 2018;Thye et al, 2010) for further study of the evolutionary dynamics between host and pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…These enable detection of single nucleotide polymorphisms (SNPs) throughout the genome that show statistical associations with pathogen infection. In addition to identifying associations at known immune loci (Fellay et al, 2007;He et al, 2015;Wong et al, 2010), GWAS approaches may reveal novel candidate genes (Fu et al, 2012;Ravenhall et al, 2018;Thye et al, 2010) for further study of the evolutionary dynamics between host and pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies with larger sample sizes are needed to understand the unpinning genetic architecture of severe malaria susceptibility/resistance phenotype. were obtained from the general population (15)(16)(17)(18). All the samples were genotyped on Illumina Omni 2.5M array and were provided in VCF format.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a number of severe malaria GWASs have recently been implemented in malaria endemic areas in Africa and reported a number novel variants (15)(16)(17)(18), little is known about the proportion of h 2 g and its distribution across chromosomes, functional regions and allele frequency spectrum. We hypothesize that malaria susceptibility and resistance is a complex trait that is mainly under polygenic control.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a strong association signal in CSMD1 gene on chromosome 8 was evidenced in mild 368 malaria attacks analysis. No functional evidence was found by FUMA for this association signal; 369 however, an association signal in CSMD1 was recently found in a GWAS of severe malaria in 370 Tanzania (20); it is a transmembrane protein, assumed to be a tumor suppressor gene (52), and is 371 also associated with phenotypes as diverse as blood pressure (53) and schizophrenia (54) but there 372 is as of yet no clear scenario to explain its potential role in malaria. 373…”
mentioning
confidence: 99%
“…Among those, sickle cell trait (haemoglobin S, HbS), haemoglobin C (HbC) at homozygote 87 state, alpha+ thalassemia and glucose-6-phosphate dehydrogenase (G6PD) deficiency have been 88 associated with a protection against parasite invasion and clinical malaria attacks (7).89 Other association studies have focused on chromosomal regions linked with parasite infection levels 90 and mild malaria susceptibility, in particular 5q31-33 and 6p21-23 (8)(9)(10)(11)(12)(13)(14)(15). In this last region, TNF 91 has been the most studied candidate; NCR3, encoding a cell membrane receptor of natural killer, 92 has been also repeatedly associated with mild malaria (10,16).Since 2010, several genome-wide 93 association studies (GWAS) and meta-analysis have been published on severe malaria (17)(18)(19)(20)(21).94 These studies confirmed the involvement of previously known susceptibility genes (HBB and ABO) 95 and revealed new genes (ATP2B4, the cluster of genes GYP/FREM3, among which GYPA and 96 GYPB appear to play a central role (21)).…”
mentioning
confidence: 99%